Protocol to assess and reduce post-harvest losses in tomato value chain - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
Framework has been applied in a pilot in Nigeria on the tomato supply chain. Results were published. Conclusions are that it can be a useful tool to identify practices, causes, and indicators of food loss.